The Summer of You and Me : A Novel - Hunter, Denise, 1968- (Thorndike, Maine : Center Point Large Print, 2025)
"Five years after her husbands death, Maggie is finally ready to let go of him and the dreams she had for their future. A summer at Seabrook, where she and Ethan first became childhood sweethearts, seems the perfect time and place to find closure. Plus, she gets to spend time with his family, the Reynoldses, whom she loves like her own. Unbeknownst to Maggie, her brother-in-law, Josh Reynolds, has been in love with her since they first met all those years ago. But his brother ultimately won Maggies heart, and Joshs unrequited love has ruined all his relationships. If Maggie is ready to move on, then Josh is ready to lay it all on the line and come clean about his true feelings for her. But his plans soon get put on hold when, shortly after Maggie returns to Seabrook, she runs into a man who could pass for Ethans twin. But he disappears into the amusement park crowd before she can confront him. The event rattles Maggie, stirs up impossible questions, and sends her on a quest to discover the mans true identity. But the search ends up raising more questions than answers and soon Maggie isnt sure she wants those answers after all."--
Keywords: Widows -- Fiction; Man-woman relationships -- Fiction; First loves -- Fiction; Extended families -- Fiction; North Carolina -- Fiction; Christian fiction; Romance fiction; Large print books